1999
DOI: 10.1128/jcm.37.5.1361-1365.1999
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Borrelia burgdorferi in Ixodes ricinus Ticks in Urban Recreational Areas of Helsinki

Abstract: Lyme borreliosis, an infection caused by the tick-borne spirocheteBorrelia burgdorferi, is a major health problem for populations in areas of endemicity in the Northern Hemisphere. In the present study we assessed the density of ticks and the prevalence ofB. burgdorferi sensu lato among ticks in popular urban recreational areas of Helsinki, Finland. Altogether 1,688 Ixodes ricinus ticks were collected from five areas located within 5 km of the downtown section of Helsinki, and 726 of them (303 nymphs, 189 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 27 publications
4
40
2
1
Order By: Relevance
“…infection in the ticks of Turku and the Turku archipelago was 5% (range 0-11.6%). Earlier, Junttila et al have reported an average infection rate of 32% (range 19-55%) in ticks collected from Helsinki city parks (23). One reason for these discrepant findings may be that the method repertoire used by Junttila et al was more extensive than ours.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…infection in the ticks of Turku and the Turku archipelago was 5% (range 0-11.6%). Earlier, Junttila et al have reported an average infection rate of 32% (range 19-55%) in ticks collected from Helsinki city parks (23). One reason for these discrepant findings may be that the method repertoire used by Junttila et al was more extensive than ours.…”
Section: Discussioncontrasting
confidence: 62%
“…occur in Europe (19)(20)(21). In Finland, Borrelia garinii and Borrelia afzelii have been found to be the most prevalent genospecies (22,23).…”
mentioning
confidence: 99%
“…In 15 patients, the genospecies was B. garinii, in 6 patients B. afzelii, and in one patient both genospecies were found. This was an inverse genospecies distribution of B. garinii and B.afzelii as compared to that reported for Finnish tick isolates by Junttila et al (17). They studied 726 ticks collected from urban parks in Helsinki and found B. afzelii in 99 ticks and B. garinii in 36 ticks.…”
Section: Discussionsupporting
confidence: 54%
“…One explanation for the high incidence may be the rural nature of the survey area. However, evidence is accumulating that ticks can be abundant and their rates of infestation with B. burgdorferi high even in highly urban environments (17). In Finland, about 1-2 million people live in areas where Lyme borreliosis is as endemic as in the survey area.…”
Section: Discussionmentioning
confidence: 99%
“…Bg Å218, a Finnish tick isolate, has been described previously elsewhere [29]. The bacteria were grown in liquid Barbour-Stoenner-Kelly II medium and passaged weekly.…”
Section: Bacterial Culturementioning
confidence: 99%